Do soccer and Zumba exercise improve fitness and indicators of health among female hospital employees? A 12‐week RCT. Issue 6 (24th October 2013) - Barene, S.; Krustrup, P.; Jackman, S. R.; Brekke, O. L.; Holtermann, A.
<x xml:space="preserve">Abstract</x> This randomized controlled study investigated the effectiveness of soccer and Zumba on fitness and health indicators in female participants recruited from a workplace. One hundred seven hospital employees were cluster‐randomized to either a soccer group (SG), Zumba group (ZG), or control group (CG). Intervention effects for the two training groups were compared with CG. The training was conducted outside working hours as 2–3 1‐h sessions per week for 12 weeks. Peak oxygen uptake (VO2peak), fat percentage, fat mass, bone mineral content, and plasma osteocalcin were measured before and after the intervention period. Based on intention‐to‐treat‐analyses, SG significantly improved the VO2peak relative to body mass (5%; P = 0.02) and decreased heart rate during 100‐W cycle exercise (−7 bpm; P = 0.01), total body fat percentage (−1.1%; P = 0.002), and total body fat mass (−1.0 kg; P = 0.001) compared with CG. ZG significantly improved the VO2peak relative to body mass (5%; P = 0.03) and decreased total fat mass (−0.6 kg; P < 0.05) compared with CG. Plasma osteocalcin increased in SG (21%; P < 0.001) and ZG (10%; P = 0.01) compared with CG. The present study indicates that workplace initiated short‐term soccer training as well as Zumba outside working hours may result in fitness and modest health benefits among female hospital employees.